Desain Fasilitas dan Lansekap Kafe RASA Medan Untuk Meningkatkan Kenyamanan dan Pengalaman Pengunjung - Baihaqi, Dayan Hakam; Khairi, Nurhafizhah (Politeknik Pariwisata Medan, 2024)
Cafes are one of the culinary businesses that are now in great demand by customers. Good landscape design and guaranteed business feasibility will provide security and comfort for visitors. One of the cafes that is a destination for visitors in Medan is the Rasa cafe. This study aims to understand in depth the application of landscape design and business feasibility standards at the Rasa cafe and the factors that influence its success based on the Regulation of the Minister of Tourism and Creative Economy (Permenparekraf) Number 4 of 2021. This study uses a qualitative approach with a case study method. Data collection was carried out through interviews, documentation and field observations and using scientific journals as references. The results of this study indicate that the Rasa cafe has met business feasibility standards and has a minimalist design and landscape that has indoor and outdoor areas that are shady and provide comfort for visitors who come. However, because the location is not crowded, this cafe must increase its promotion so that it is better known to the general public.